Experimental comparison between four CO2-based transcritical Rankine cycle (CTRC) systems for engine waste heat recovery. (15th October 2017) - Shi, Lingfeng; Shu, Gequn; Tian, Hua; Huang, Guangdai; Chen, Tianyu; Li, Xiaoya; Li, Daiqiang
Highlights: Experimental comparison between four CTRC systems. Great improvement was obtained by adding a preheater and a regenerator. 2% absolute increase of engine efficiency was achieved by the PR-CTRC. Combined analysis of cooling load for engine and CTRC system. Abstract: In order to recover waste heat from both exhaust gas and coolant water of engine, and improve system thermal efficiency, four CO2 -based transcritical Rankine cycle (CTRC) systems with kW-scale power output were constructed, including a basic CTRC (B-CTRC), a CTRC with a regenerator (R-CTRC), a CTRC with a coolant preheater (P-CTRC) and a CTRC with both the preheater and the regenerator (PR-CTRC). Experimental comparison between the four systems was presented based on an expansion valve, which can make system operate steadily and obtain the potential of net power output. Energy analysis, exergy analysis and cooling load analysis for the four systems were conducted at various pressure ratios. The results indicated that the PR-CTRC owned the highest potential of net power output, thermal efficiency and exergy efficiency, whose estimation reached up to 3.47 kW, 7.8% and 17.1%, respectively. In view of the linear fitting value at the same pressure ratio of 1.65, net power output, thermal efficiency and exergy efficiency of the PR-CTRC achieved increase of 100.6%, 69.6% and 79.5% versus that of the B-CTRC, respectively. Furthermore, the PR-CTRC required the lowest total cooling load jointly considering the engine and the CTRC system. The P-CTRC and the R-CTRC also had better thermodynamic performance than the B-CTRC did, but it was worse than that of the PR-CTRC. The preheater had more active effect on the power output, exergy efficiency and cooling load of the engine, and the regenerator contributed more to the thermal efficiency and cooling load of the CTRC. In summary, two main aspects of improvement for the engine were achieved by the PR-CTRC: thermal efficiency of the engine increased from 39.4% to 41.4% by the additional power output of bottoming system, and about 50% cooling load of the engine could be reduced and converted to preheat input of the CTRC system.